2013
DOI: 10.1105/tpc.113.114538
|View full text |Cite
|
Sign up to set email alerts
|

Zeaxanthin Binds to Light-Harvesting Complex Stress-Related Protein to Enhance Nonphotochemical Quenching in Physcomitrella patens

Abstract: ORCID IDs: 0000-0003-4818-7778 (A.A.); 0000-0002-0803-7591 (T.M.); 0000-0003-4735-8811 (R.B.).Nonphotochemical quenching (NPQ) dissipates excess energy to protect the photosynthetic apparatus from excess light. The moss Physcomitrella patens exhibits strong NPQ by both algal-type light-harvesting complex stress-related (LHCSR)-dependent and plant-type S subunit of Photosystem II (PSBS)-dependent mechanisms. In this work, we studied the dependence of NPQ reactions on zeaxanthin, which is synthesized under light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 74 publications
8
88
0
1
Order By: Relevance
“…HPLC analysis on eluted slices showed that fractions enriched in PpLHCSR1 protein were characterized by a very high Chl a/b ratio with values between 8 and 24 (Fig. 6, C and D), suggesting that PpLHCSR1 could bind Chl b in a substoichiometric amount only as reported previously for Chlamydomonas reinhardtii LHCSR3 proteins (20) and native LHCSR1 from P. patens (22).…”
Section: Expression and Purification Of Pplhcsr1 His Tag By Affinitymentioning
confidence: 75%
See 3 more Smart Citations
“…HPLC analysis on eluted slices showed that fractions enriched in PpLHCSR1 protein were characterized by a very high Chl a/b ratio with values between 8 and 24 (Fig. 6, C and D), suggesting that PpLHCSR1 could bind Chl b in a substoichiometric amount only as reported previously for Chlamydomonas reinhardtii LHCSR3 proteins (20) and native LHCSR1 from P. patens (22).…”
Section: Expression and Purification Of Pplhcsr1 His Tag By Affinitymentioning
confidence: 75%
“…Absorption spectra of B1 and B2 of oeLHCSR1 showed a red-shifted Qy absorption peak when compared with the corresponding fractions from WT (Fig. 3, A-D); because a red-shifted spectrum is a typical characteristic of LHCSR1 protein (20,22), this suggests LHCSR1 migrates in the region of B1 with monomeric LHCs. This characteristic was more evident in the case of N. benthamiana (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In P. patens, LHCSR is independently functional in addition to PsbS to induce qE [8,50,51]. Unlike its orthologs in C. reinhardtii [45], the qE activity of PpLHCSR is largely reliant on the accumulation of zeaxanthin [52 ]. The two PpLHCSR isoforms, LHCSR1 and LHCSR2, are more responsible for quenching under high light or low temperature, respectively [53].…”
Section: Introductionmentioning
confidence: 99%